Sistematización de la puesta en escena en inglés “wHOMEver” del curso teatro contemporáneo 2019 – II - Higuera Vallejo, Andry Yuressica (Universidad Antonio Nariño, 2022)
This degree work is the systematization of the experience of the creation process of the work "wHOMEver", in English, of the contemporary theater course of the Antonio Nariño University, where dance theater was worked on. Aspects that influenced the staging are reflected, analyzed and identified, taking into account the EAPEAT (Pedagogical Artistic Experience of the Current State of Tradition), at the Manizales International Festival in 2019. Taking into account the methodology of Oscar Jara in his "step by step" to systematize processes and Manuel Ghiso, in "deepen reflection"